Exploring marketing channels and market margins of tuna species: A case study of Negombo fishery harbour in Sri Lanka in 2018 - Edirisinghe, K.; Wansapala, J.; Wickramasinghe, I.; Warahena, A.S.K. (Faculty of Science University of Ruhuna, 2018)
This study was carried out to determine the domestic level marketing channels, marketing cost, and marketing margin for four commercially important marine fish species in Negombo fishery harbour, Western Province, Sri Lanka, with a focus on marketing efficiency. Data related to fish catch and prices were collected by direct observation during the period of January to December 2018. About 80 to 105 tons of fish catch per day were being landed. The annual average wholesale prices of fish (kg -1 )g varied from LKR 450 to 670 for Yellowfin tuna, LKR 233 to 414 for Skipjack tuna, LKR 320 to 385 for Frigate tuna, and LKR 140 to 190 for Indian scad, which is typical market behaviour. Though the net profit per 100 kg of fish received by the wholesaler was higher than the assembler, the retailer has made a significant amount of profit, nearly six times higher than the assembler. Ten marketing channels were identified from fish producers to the ultimate consumer and some channels involved more than three intermediaries. As typical for long marketing channels, high prices were paid by the consumer for the low freshness quality of fish. Though, the retail price of skipjack tuna at the Negombo landing center is moderately correlated (r=0.634), the other three fish species did not give a clear indication. Thus, the price factor of selected marine fish at the landing site was not having a significant impact on the market integration. Consumers were concerned about both price and quality when purchasing the fish. To improve the marketing efficiency of the marine fish market, it is recommended to implement shortening of the fish market channel with less involvement of intermediaries and to develop the fish market facilities appropriately.
Keywords: Consumer preference, fish price, market efficiency, Negombo harbour.